Cognitive radio and dynamic spectrum access - Berlemann, Lars (John Wiley & Sons, 2009)
Cognitive Radio for Dynamic Spectrum Access gives a comprehensive overview of the main concepts behind radio spectrum regulation, dynamic spectrum access and cognitive radio. Spectrum measurements are introduced to illustrate the inefficiencies in today's spectrum usage and the book also discusses enablers for horizontal and vertical spectrum sharing. Among others a game-theory-based approach for spectrum sharing is described and evaluated. Institution and standardisation approaches in academic research and industry are highlighted including IEEE SCC41, 802.11k/n/s/y and 802.22 which lead towards commercial exploitation of cognitive radio. In conclusion, this book looks at the initial steps towards the vision of true cognitive radio and the potential impact on telecommunication business. * Introduces the benefits and challenges of cognitive radio * Presents cognitive radio in research and industry and covers implications for operators from the perspective of a telecom operator * Examines how cognitive radio techniques will considerably change the wireless communication market.